A Study of the Friction Coefficients of Unidirectional and Woven Carbon Fibre/Epoxy Composites. Issue 4 (May 2016) - Cheng, B.; Kortschot, M.
The friction coefficients of unidirectional carbon fibre/epoxy composites (with the fibres parallel and antiparallel to the sliding direction) were measured under severe abrasive conditions. Aluminium oxide sandpapers with three different grits (36, 80, and 120) were used as the counter surfaces. Three different applied loads (5, 10, 22N) and two different sliding speeds (2 m/s, 4 m/s) were selected as the testing parameters. Under these conditions, composites with fibres parallel to the sliding direction had a significantly lower friction coefficient. Using the measured friction coefficients of unidirectional composites, a modified rule of mixtures equation was developed to predict the friction coefficients of woven carbon fibre/epoxy composites under the conditions. The model is based on the hypothesis that the more wear resistant regions of the weave (fibres that are parallel to the sliding direction in this case) would protect the less wear resistant regions (fibres that are antiparallel to the sliding direction), and that the load is redistributed to yield equal wear rates for the two zones. It was found that the model was able to accurately predict the friction coefficients of the woven composites for the abrasive conditions tested in this study.